REPRESENTASI NILAI BUSHIDO KEBERANIAN (YU) DALAM ANIME (ANALISIS SEMIOTIKA C.S. PIERCE) - Mahendra, Faisal Arif; Ali, Mohammad (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2023)
This study aims to describe the representation of the courage (yu) value of the bushido contained in the characters Rengoku Kyojurou from Kimetsu no Yaiba Movie: Mugen Ressha-hen, Ikoma and Kurusu from Koutetsujou no Kabaneri Movie 3: Unato Kessen, and Fujimaru Ritsuka from Fate / Grand / Order: Shinsei Entaku Ryouiki Camelot. The research method used in this study is descriptive qualitative with Charles Sanders Pierce's semiotic analysis approach. The data were analyzed using Pierce's triadic model of signs in the form of representaments (signs), objects and interpretants (interpreters). Based on the results of the study, there is a representation of the value of bushido yu in each character which has signs in the form of actions that display high courage and self-confidence in each character. Keywords: Bushido, Representation, Anime, Semiotic